Comparative biology and production costs of Podisus nigrispinus (Hemiptera: Pentatomidae) when fed different types of prey - De Bortoli, Sergio A. [UNESP]; Otuka, Alessandra K. [UNESP]; Vacari, Alessandra M. [UNESP]; Martins, Maria I. E. G. [UNESP]; Volpe, Haroldo X. L. [UNESP] (Academic Press Inc. Elsevier B.V., 2011)
The objective of our work was to identify the prey that offers optimum production of the predator, Podisus nigrispinus (Dallas). The cost of predator production was determined for each prey. We test the hypothesis that prey types supporting optimal development do not facilitate cost-effective rearing of P. nigrispinus. Second-instar nymphs of P. nigrispinus were reared in 1000-ml transparent plastic containers and maintained under controlled conditions (temperature, 25 +/- 1 degrees C; photophase duration, 12 h; relative humidity, 70 +/- 10%), and the following biological aspects were evaluated: nymph viability, length of the nymphal period, and weight of fifth-instar nymphs. The adults were isolated in pairs (one female and one male) in Petri dishes, and the following biological aspects were evaluated: lifespan, adult weight after emergence, number of eggs per female, egg mass in females, number of eggs per egg mass, durations of the pre-oviposition, oviposition, and post-oviposition periods, viability, and length of the embryonic period. on the basis of our results, we conclude that the prey that leads to optimal development of P. nigrispinus is the larvae of Diatraea saccharalis (Fabr.), and the most cost effective prey for rearing P. nigrispinus is the larvae of Musca domestica L. Crown Copyright (C) 2011 Published by Elsevier B.V. All rights reserved.
Keywords: Heteropteran predator; Mass rearing; Biological control; Asopinae